2016
DOI: 10.3141/2573-12
|View full text |Cite
|
Sign up to set email alerts
|

Specification Limits and Pay Adjustment for Longitudinal Joint Density of Asphalt Pavements: Case Study in New Jersey

Abstract: This paper summarizes a case study on developing specification limits and pay adjustments for the longitudinal joint density of asphalt pavements. The existing joint density specifications used by various agencies first were reviewed for the minimum joint density requirements and the corresponding pay adjustments. Laboratory tests were conducted to measure air voids of field cores taken from selected field projects with the saturated surface dry method (AASHTO T 166) and the automatic vacuum-sealing method (AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…In traditional asphalt mixture gradation designs, air voids in the asphalt mixture are the most important indexes of volumetric properties; they can also affect the performance of an asphalt pavement. Several studies have been conducted to determine the effect of air voids on the performance characteristics of asphalt mixtures, including fatigue cracking and rutting [63]. These reports suggest that the road service life decreases by approximately one year for every 1% increase in the air void content.…”
Section: Road Test Performancementioning
confidence: 99%
“…In traditional asphalt mixture gradation designs, air voids in the asphalt mixture are the most important indexes of volumetric properties; they can also affect the performance of an asphalt pavement. Several studies have been conducted to determine the effect of air voids on the performance characteristics of asphalt mixtures, including fatigue cracking and rutting [63]. These reports suggest that the road service life decreases by approximately one year for every 1% increase in the air void content.…”
Section: Road Test Performancementioning
confidence: 99%
“…Major findings by Fleckenstein et al (2002) and Mallick & Daniel (2006) indicate that although, the joint maker technique and adhesive treated joints had the lowest densities of all the joint improvement methods studied; they had lower permeability values and the best performance under long-term performance study compared to joint constructed using the conventional methods. Similar findings by Wang et al (2016) and Williams (2011) suggested that while asphalt pavement longitudinal joint treated with the joint stabilizer using polymerized emulsion products had the least density; it ironically had the best performance. Thus, one would argue that the ability to limit the intrusion of water into the body of the asphalt concrete could lead to a better performing and more durable pavement system.…”
Section: Permeability and Longitudinal Joint Construction Practicessupporting
confidence: 62%
“…By default, there is a theoretical notion that the application of grid reinforcements inherently reduces and weakens the interlayer bonding strength of the HMA overlay, which may not be the case. However, most of the literature reviewed provided shear-bond strength data on un-reinforced HMA overlays, mostly based on laboratory prepared-samples [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Based on field core testing, Wilson et al [17] measured a shearbond strength range of 15-95 psi with satisfactory in-service (field) interlayer bonding performance [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…From testing both field cores and laboratory prepared-samples with different grid-reinforcement materials, Walubita et al [15] recorded interlayer shear-bond strengths varying from 33 to 175 psi. Overall, shearbond strength values ranging from as low as 15 psi to as high as 217 psi were reviewed in the literature, mostly for un-reinforced HMA and subjected to varying laboratory test methods/conditions [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Furthermore, different institutions, states, and countries seem to have different criteria for characterizing and quantifying the interlayer bond strength in HMA; ranging from a tolerable 40 psi [17] to a more stringent shear-bond strength value of 100 psi [18,19].…”
Section: Literature Reviewmentioning
confidence: 99%